Surgical Management for Fecal Incontinence - Anandam, Joselin L. (Clinics in Colon and Rectal Surgery, 2014)
Fecal incontinence is a socially debilitating condition that can lead to social isolation, loss of self-esteem and self-confidence, and depression in an otherwise healthy person. After the appropriate clinical evaluation and diagnostic testing, medical management is initially instituted to treat fecal incontinence. Once medical management fails, there are a few surgical procedures that can be considered. This article is devoted to the various surgical options for fecal incontinence including the history, technical details, and studies demonstrating the complication and success rate.
Keywords: Fecal incontinence; Anal sphincteroplasty; sacral nerve stimulation; artificial anal sphincter